Upaya Peningkatan Hasil Belajar IPA Melalui Metode Demonstrasi - Inti Lestarai (Academy of Education Journal, 2018)
The purpose of this Classroom Action Research is to improve student learning outcomes in grade 1 SD Negeri 2 Karanggayam Kidul Kec Purwojati, through the application of demonstration methods (experiments) so that natural science learning about material objects that can be changed in shape is achieved. The research design is carried out through two cycles, starting from planning, implementation, action, observation, reflection and proceed with planning the next cycle. The results of this class action improvement is the average value of student learning outcomes have increased from the initial condition of 60.1 can increase to 71.5 in cycle I. While in cycle II to be 75.6. In terms of completeness in the initial study 16 students completed, cycle I 26 students completed and cycle II 33 students completed from 34 students with completeness values of 70 and above. Based on the findings of the results of this study it can be concluded that the application of the demonstration method (experiment) in natural science learning about material objects which can be changed in shape can improve student learning outcomes in grade 1 SD Negeri 1 Karangtalun Kidul